Fiscal policy in the management of hydraulic resources: A computable general equilibrium model - Gutiérrez Andrade, Miguel Ángel; Venegas Martínez, Francisco; Bravo Pérez, Héctor Manuel (Estudios Económicos de El Colegio de México, 2005)
We examine the impact of fiscal policy in the management of water resources by using a computable general equilibrium model. Several comparative static exercises are carried out to assess the effects of a particular fiscal policy economic welfare. Finally, we state a set of fiscal policy recommendations for the efficient management of water in the production process for the Mexican case.